MINAT BELI INTERNATIONAL FASHION BRAND DI INDONESIA - Oktaviana, Ineke; Rahmawan, Ginanjar (Politeknik Negeri Ambon, 2023)
This study aims to determine the effect of fashion lifestyle, international brand image, and consumer attitudes on buying interest of international fashion brands. The international fashion brands referred to in this study are fashion that are worldwide. This research contributes to the development of fashion , in line with the government's goal of promoting local products. The sampling technique used in this study was purposive sampling with a total sample of 166 people. Respondents are people who are interested in buying fashion that are worldwide. The data used is primary data using a questionnaire instrument. The analysis techniques used are validity and reliability tests, classical assumption tests, and multiple regression tests using the SPSS 21 program. Based on the results of the data testing conducted, it shows that Fashion Lifestyle partially has a significant effect on the interest in buying local fashion products worldwide, International brand image on the worldwide interest in buying local fashion products, the attitude of consumers towards the worldwide interest in buying local fashion products, as well as fashion lifestyle, international brand image, and consumer attitudes simultaneously affect the intention to buy local fashion products worldwide.